If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + -1) + 2x = 61 + -1x Reorder the terms: 5(-1 + 2x) + 2x = 61 + -1x (-1 * 5 + 2x * 5) + 2x = 61 + -1x (-5 + 10x) + 2x = 61 + -1x Combine like terms: 10x + 2x = 12x -5 + 12x = 61 + -1x Solving -5 + 12x = 61 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -5 + 12x + x = 61 + -1x + x Combine like terms: 12x + x = 13x -5 + 13x = 61 + -1x + x Combine like terms: -1x + x = 0 -5 + 13x = 61 + 0 -5 + 13x = 61 Add '5' to each side of the equation. -5 + 5 + 13x = 61 + 5 Combine like terms: -5 + 5 = 0 0 + 13x = 61 + 5 13x = 61 + 5 Combine like terms: 61 + 5 = 66 13x = 66 Divide each side by '13'. x = 5.076923077 Simplifying x = 5.076923077
| 6x-8=-4x-48 | | 3(3n+4)=-4h-16 | | 33=-6-3x | | 5x/6-3=x-10 | | 9xz=1 | | 5+2(n+1)=2 | | N/13=8/17 | | -7(x+7)-5=-54 | | 2x-xy=3(2y-xy) | | -1+21x+32=27x-5 | | -18v=-234 | | 4(3z+2)-9=107 | | 2(3x-6)=3(5x-4) | | 0=5-5x | | Ax+b=cx-b | | 5(x-3)+1=6x-31 | | 9x+12y=4 | | 1/4-1=11 | | 1/4-1=1o1 | | 25x-5=40x+4 | | (8z-7)(2-4)= | | -5x+4(7+4x)=36+7x | | 4x+7=31-2x | | 1/4g-1=11 | | 5(x+3)=0 | | 160=16n | | y=(x^2)+2x+4 | | 11+r=13 | | 2x^2/24 | | f(3)=3+5x+2 | | 3(k+1)=4k-4 | | n+17=7 |